EVALUATION OF METALLIC MATERIALS PLASTICITY BY DYNAMIC INDENTATION METHOD - V. A. Rudnitsky; A. P. Kren; G. A. Lantsman (Литьë и металлургия, 2017)
The method of plasticity test of metallic materials realized by means of a dynamic dimpling of material by a spherical tip is offered. The measured value of plasticity is defined by a ratio of plastic and complete deformations in the formed indentation which considers influence of an elastic modulus of material. The dependence connecting plasticity and dynamic hardness of materials is received. Experiments on metals from 70 to 380 GPA having an elastic modulus and hardness up to 62 HRC are made.